2022
DOI: 10.3390/atmos13020271
|View full text |Cite
|
Sign up to set email alerts
|

Transpiration of a Tropical Dry Deciduous Forest in Yucatan, Mexico

Abstract: The study of forest hydrology and its relationships with climate requires accurate estimates of water inputs, outputs, and changes in reservoirs. Evapotranspiration is frequently the least studied component when addressing the water cycle; thus, it is important to obtain direct measurements of evaporation and transpiration. This study measured transpiration in a tropical dry deciduous forest in Yucatán (Mexico) using the thermal dissipation method (Granier-type sensors) in representative species of this vegeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
4
0
1
Order By: Relevance
“…The association of low K to high vegetation stem count and vice versa (Tables 1 and 4) may suggest that transpiration had a significant influence on baseflow recession [17,19] and that stand transpiration could be more strongly governed by stem count instead of basal area [59,60]. These findings differed from the recent convention [22,61,62], but it is substantiated by others [63] citing that an increase of basal area does not necessarily equate a proportional increase of sapwood area. Contrary to past studies where transpiration show strong relationships with basal area [64], the association of low K to high stem density in this study may reflect the higher growth rates, carbon fixation, and water uptake of young trees compared to mature trees which, despite their large size, have reached a plateau [63,65,66].…”
Section: Baseflow and K In A Gradient Of Land-use Disturbancesmentioning
confidence: 89%
“…The association of low K to high vegetation stem count and vice versa (Tables 1 and 4) may suggest that transpiration had a significant influence on baseflow recession [17,19] and that stand transpiration could be more strongly governed by stem count instead of basal area [59,60]. These findings differed from the recent convention [22,61,62], but it is substantiated by others [63] citing that an increase of basal area does not necessarily equate a proportional increase of sapwood area. Contrary to past studies where transpiration show strong relationships with basal area [64], the association of low K to high stem density in this study may reflect the higher growth rates, carbon fixation, and water uptake of young trees compared to mature trees which, despite their large size, have reached a plateau [63,65,66].…”
Section: Baseflow and K In A Gradient Of Land-use Disturbancesmentioning
confidence: 89%
“…Therefore, ignoring the radial variation of J s may produce an error when scaling up from J s to T . However, previous studies in tropical forests that use similar sap flow sensors only measured J s at the outer sapwood because of the unknown pattern of sapwood area in tropical tree species ( Horna et al, 2011 ; Raquel Salas-Acosta et al, 2022 ). In addition, most tropical trees have diffuse-porous wood without distinct annual rings and tend to have a sap flow rate that is similar along the radial sapwood depth ( Lu, Urban & Ping, 2004 ).…”
Section: Methodsmentioning
confidence: 99%
“…The RDA, in fact, revealed a more significant influence of temperature (maximum and minimum) than precipitation on vegetation. Temperature in the Yucatan Peninsula plays an important role in controlling plant phenology and physiology [38,39], where it has been observed that plant evapotranspiration in tropical dry deciduous forests, driven by solar incidence, is relatively similar between the dry and rainy seasons [40]. Thus, we consider that temperature plays a key role in coastal vegetation dynamism, since prolonged episodes of droughts (when freshwater is unavailable) during the dry season may be endured by plants with a higher tolerance to salinity, thus leading to minimal plant cover disturbance between seasons.…”
Section: Spatial and Temporal Vegetation Cover Density Variability In...mentioning
confidence: 99%